Bimbingan Konseling Berpengaruh terhadap Akhlak Siswa Kelas II pada Mata Pelajaran Aqidah Akhlak - Tjipto Djuhartono; Bakti Toni Endaryono (SAP (Susunan Artikel Pendidikan), 2021)
This study aims to determine How Counseling Guidance Affects the Morals of Students at SDIT Assalam Bekasi Regency. The method used in this study is the Quantitative Method and literature study with the preparation, implementation, and final stages. The data collection techniques used were observation, interviews, and distributing questionnaires to a population of 20 students by taking the population later for research. The results of this study showed that first, the effect of Counseling Guidance on the Morals of Class II Students at SDIT Assalam was very good in terms of motivation for implementing home learning and had something very potential in spurring students' morals, but not good from the individual side of students. Second, from the results of the data analysis questionnaire, it was known that the Counseling Guidance on the Morals of Students in Class II Aqidah Morals Subjects at SDIT Assalam was obtained by 52%. These results indicated that there was a significant relationship between counseling guidance and student morals. and the remaining 48% was influenced by other factors such as student background, family and so on.